THE APPLICATION OF THE PRINCIPLE OF UTMOST GOOD FAITH IN PYRAMID SCHEME BUSSINES PRACTICE - Tuti Rastuti; Gandhi Pharmacista (Lembaga Penelitian Universitas Pasundan, 2019)
This study focuses on the study of media development against misinformation and contains the best elements. This situation has been exploited by the actors / activities that conduct business pyramid scheme invetation. The social growth media plays an important role in the development of the pyramid in which the givers / promoters in attracting the public interest, carried out in a pattern that is shared with the public figures using the ambassador's brand, the notes boost offerees to join other aspects such as legality and prospects social media investment, social media, culture, culture, culture, culture, culture, socialization, promotion, promotion, promotion, promotion, promotion. This study focuses on the study of violations of law against the principle of utmost good faith in the fraudulent practices of pyramid schemes used by the offeror when conducting recruitment. This fraudulent practice in its development uses social media as a misleading means of conveying information. To appeal to a widely used pattern of inviting offeree by accentuating the public figure being brand ambassador, thus boosting offeree trust to join. The objective of the study was to criticize mediamorphosis in eradicating fraudulent pyramid schemes in business investment. This research uses empirical juridical method with normative juridical approach. Observation activities support the search for legal literature. The results show that, (1) misleading information is a violation of the principle of utmost good faiht used when the promoter offers and recruits the offeree into the fraudulent practices of the pyramid scheme business; (2) social media into commodities and promotional support instruments for offerors in the fraudulent practices of pyramid scheme business investments; offeree joins a prominent pyramid promotion scheme without considering the legality and prospects of the investment.